Reimagining Curriculum Studies A Mosaic of Inclusion - Blumenfeld-Jones, Donald S. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book addresses the crucial issue of how we value and deploy the idea of "freedom" that underlies contemporary curriculum studies. Whether we are conventional curriculum thinkers who value knowledge development or favor a Deweyan, individualist orientation toward curriculum or are a critical social justice curriculum thinker, at the heart of all these orientations and theorizing is the value of "freedom." The book addresses "freedom" through novel sources: the work of Martin Buber on education, Julia Kristeva on the uses of imagination and the female/male dialectic, Emmanuel Levinas' unique approach to ethics, and more. Readers will find new ways to understand freedom and the world of ethical life as informing curriculum thinking. It provides a more ecumenical vision that can draw our differences together. It helps readers to reconsider ourselves in fruitful ways that can bring more relevance and substance to the field.
Chapter 1. The Illness of Our World: A Critique of Curriculum Studies -- Chapter 2. Mosaical Thinking and Curriculum Theory -- Chapter 3. Dialectical Processes Toward Freedom -- Chapter 4. Wild Imagination and the Critical Project -- Chapter 5. Freedom All Too Human -- Chapter 6. Pure Imagination and Freedom -- Chapter 7. Creativity and Aesthetic Consciousness in Teacher Education -- Chapter 8. Identity, Self and Liberation -- Chapter 9. Reimagining Time -- Chapter 10. Epilogue: Living a Mosaical Life, Living Ironically.
Keywords: Education-Philosophy.; Education-Curricula.; Education-Research.; Educational Philosophy; Curriculum Studies; Philosophy of Education; Research Methods in Education